Bilateral paediatric optic nerve sheath meningioma. Issue 8 (5th August 2022) - Hurley, Daire John; Whitlow, Shane; O'Rourke, Declan; Flitcroft, Ian
Abstract : At birth, the patient was noted to have microphthalmia and optic atrophy in her left eye with no apparent cause. In early childhood, the vision in that eye began to deteriorate. A few years later, disc swelling was noted in the contralateral right eye. Neuroimaging was normal and a subsequent lumbar puncture found borderline high opening pressure. Vision and visual fields in the right eye remained stable until the patient was in early adolescence when she started to complain of blurred vision. Her pattern visual evoked potential showed a 75% reduction in P100 amplitude compared with the previous year. Repeat neuroimaging was suggestive of bilateral meningiomas and a biopsy was performed to confirm this. Subsequently, the patient was treated with proton beam therapy to salvage vision in her right eye. This is a novel case of meningioma presenting with enophthalmos due to contraction of the retrobulbar optic nerve.